Smart Medicine Box With Mobile Application - Ahmad, Nur Azliza; Asmawi, Norizzmier; Zairul, Arsyad; Amran, Ammar (Multidisciplinary Applied Research and Innovation, 2023)
A lot of medical issue is happen due to the facts that a lot of patients needto deal with sorting a large amount of medicine everyday. This is the main reason ofthe project Smart Medicine Box (SMB). This protoype is used to help the patients inthe area of remembering and helping people to take medicine. Main focus of SMB isfor the patients who need medical attentions more than the other. SMB isprogrammable through mobile application that enable the doctor to deternmined theschedule for the patients to take the medicine. The SMB contains twenty-one partitionthat have twenty-one LED for the user can set the schedule based on week. SMB willremind the patient by sending the notification through the mobile application and alsothe LED will lights up when the time for eat the medicine have come.